Boron Fractions in a Vertic Ustochrept as Influenced by Thirteen Years of Fertilization and Manuring - S.P. Datta, K.B. Polara, H.K. Sobhana and Muneshwar Singh, Abir Dey, B.S. Dwivedi, M.C. Meena (Journal of the Indian Society of Soil Science, 2017)
Soil and plant samples were collected after harvest of wheat in 2010 from a long-term experiment on groundnut-wheat sequence that continued since 1996-97 on a Vertic Ustochrept at Junagadh Agricultural University, in order to study the distribution of boron (B) in different fractions and their contribution towards B availability in soil and B uptake by wheat. Treatments included N alone, NP, NPK, 150% of recommended NPK, NPK+farmyard manure (FYM) and an unfertilized control. Five soil B fractions were determined along with hot CaCl2-extractable (available) B. Specifically adsorbed and organically bound B fractions were significantly greater under continuous use of NPK+FYM compared with other treatments, resulting in higher values of available B under NPK+FYM treatment. Soil organic C and cation exchange capacity were the important soil characteristics that governed the distribution of soil B in different fractions. Organically bound B appeared pivotal regarding availability of native B for plant uptake.